PENDAMPINGAN SERTIFIKASI HALAL KERUPUK RAMBAK KULIT DUSUN CEGOKAN DESA WONOLELO KABUPATEN BANTUL - Imelda Fajriati; Diza Harris Pratiwi; Abdul Aziz; Prabawati, Susy Yunita (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2023)
Assistance for halal certification for Micro Small Businesses of Wonolelo Bantul leather rambak crackers has been carried out in order to support the acceleration of halal product guarantees as mandated by Law No. 33 of 2014. Micro and small business actors (MSEs) are the largest producers of food and beverage products that are subject to mandatory halal because of the increasing number of MSE commodities. The assistance method is carried out by providing socialization and education carried out in groups and individually, followed by discussion and interpretation of the identification results during the assistance process. The results of the assistance obtained that10 business actors in Cegokan, Wonolelo Bantul who were assisted to obtain halal certificates generally met the criteria for halal product processes in accordance with the provisions of the SJPH (Halal Product Guarantee System). Business actors have understood and followed the provisions in applying for halal certification. However, rambak  cracker products still have difficulty getting raw materials from halal-certified slaughterhouses. The supply of raw materials is temporarily obtained from collectors, making it relatively difficult to follow the principle of tracebelity.